Negotiating green built environment at the margins - Kerr, Thor (Curtin University, 2009)
The Creative margins described in this paper were manifested in the conceptual systems of people engaged in public discussion of the environmental and social appropriateness of a property development concept known as North Port Quay in Fremantle, Western Australia. The concept was launched publicly in May 2008 by a consortium of property developers claiming that North Port Quay would revolutionize environmentally sustainable living and achieve the highest possible rating for environmental sustainability. The consortium’s legitimization strategy relied on North Port Quay meaning green urbanism in the minds of people making representations in the public domain. An analysis of newspaper texts describes how this strategy failed when the language deployed by North Port Quay’s backers in legitimizing the project encountered a diverse variety of languages in the community of Fremantle.